The digital narrative of sustainability: transforming green hotels in Uzbekistan through targeted marketing - Sodikov , Mirziyo Odiljon ugli (Universities for Tourism and Service Association Bulletin, 2025)
This paper examines the crucial function of digital marketing tactics in enhancing and conveying the value proposition of eco-friendly hotels in Uzbekistan’s developing tourist sector. The physical execution of sustainable practices, such as resource efficiency and historical protection, is essential; yet, their commercial influence depends on good digital communication that meets the conscious consumer’s need for transparency and authenticity. The report contends that green hotels in Uzbekistan should shift from basic digital communication to targeted, narrative-focused marketing that utilizes digital platforms (SEO, social media, video content) to convert intricate sustainability accomplishments into engaging, credible guest narratives. Essential results delineate certain digital strategies—ranging from geo-targeted marketing that emphasize local Uzbek craftsmen to interactive material that illustrates energy consumption reduction—that bolster brand trust, augment bookings, and further the overarching national objective of sustainable tourism advancement.sustainable tourism development.